Pengaruh Pengembangan Karir dan Motivasi Kerja terhadap Produktivitas Karyawan di Kantor Kelurahan Cempaka Baru Jakarta Pusat - Wirdha Hardiyanti; Mahmud Syarif; Desy Tri Anggarini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study is motivated by the importance of improving the productivity of civil servants (ASN) at the sub-district level, which serves as the frontline in delivering public services. Bureaucratic reform and service digitalization demand employees to work more professionally, competently, and productively. Career development and work motivation are considered two crucial factors that influence productivity improvement. The objectives of this research are to examine the effect of career development on employee productivity, to analyze the effect of work motivation on employee productivity, and to test the simultaneous influence of both factors at the Cempaka Baru Sub-District Office, Central Jakarta. The research employed a quantitative method with a saturated sample of 48 respondents. Data were collected through online questionnaires and interviews, then analyzed using multiple linear regression, t-test, and F-test. The results show that career development has a significant positive effect on productivity (t-value 3.051 > t-table 2.014; sig. 0.004 < 0.05). Work motivation also significantly affects productivity (t-value 3.206 > t-table 2.014; sig. 0.002 < 0.05). Simultaneously, both variables significantly influence productivity (F-value 79.546 > F-table 3.20; sig. 0.000 < 0.05). Therefore, career development and work motivation can be regarded as important factors in enhancing employee productivity at the Cempaka Baru Sub-District Office.